Інституційне забезпечення інклюзивного рекреаційного природокористування: стан та вимоги - Cherchyk, Larysa; Khumarova, Nina (Dr. Viktor Koval, 2021)
Introduction. The fundamental principles of inclusive development are equality of opportunity, availability of all types of resources, equality and fairness in the distribution of income and benefits. The main message of inclusive recreational nature management is the creation of equal opportunities for the use of natural recreational resources and areas for the well-being and quality of life of people. Realization of priorities of the organization of recreational activity is not possible without the developed institutional maintenance. Defining the leading role of state authorities and civil society representatives, which establish a system of laws, rights and responsibilities, "rules of the game" and develop a set of mechanisms for their close institutionalized interaction, it is necessary to form institutions within which public representatives reconcile contradictions and determine common interests. Aim and tasks. The purpose of the study is to study the state and develop directions for the development of institutional support for inclusive tourism and recreational nature. Results. The article examines the state of institutional support for inclusive tourist and recreational nature management in Ukraine. The essence and its content are determined, the documents according to which it is determined are analyzed. The domestic legislative and normative-legal base of regulation of nature use in general and recreational in particular is studied, where separate principles of inclusive development are laid down. At the same time, a significant layer of problems remains unresolved, including the formation of new principles, forms of management to prevent the degradation of natural recreational resources, their diversity and sustainability. The interaction of formal institutions and institutes (legislative and normative base, system of state regulation, bodies of state administration and local self-government, public organizations, approved norms and norms of nature use) and informal institutions has to promote inclusive recreational nature use. Conclusions. The study of the state and directions of development of institutional support of inclusive recreational nature management allowed to determine that the implementation of an inclusive approach requires: changing the structure and stereotype of recreational needs of people and restructuring the economy of recreational nature management; reducing economic and social inequality of people to meet their recreational needs and ensuring equal access to valuable natural recreational resources.